A Phytoplankton Distribution study of Dukan basin in Sulaimani district -Kurdistan Region of Iraq. - Farkha, Trifa Kamal; Fatah1, Adil Othman (Sulaimani Journal for Pure and Applied Sciences, 2016)
This study was conducted during growing season of 2014 at Girdarash filed College of Agriculture, University of Salahaddin, Erbil, Iraqi Kurdistan Region to investigate the effect of foliar spray of three concentrations (0, 30and 60 mg.l-1 ) of iron as iron chelate (Fe – EDDHA) containing (6% of iron) and three concentrations of Kakrorich (20% nitrogen) foliar spray with concentration (0, 3, 6 mg.l-1 ) on growth characteristics of pistachio (Pistacia vera L.) cv. Musilly seedlings. A factorial experiment with three replicates was carried out in a Randomized Complete Block Design (R.C.B.D) using three seedlings for each experimental unit. The obtained results indicated that the growth characteristics increased with increasing the concentration of (Fe – EDDHA) and nitrogen as compared with control, foliar spray of iron element at (60 mgl-1 ) caused significant increase in seedling hight, seedling diameter, leaves number, leaf area, leaves area/seedling, total chlorophyll content, root length, root fresh weight, root dry weight and dry matter percentage. At the same time, application of nitrogen fertilization at (6 mg.l-1 ) gave the highest value of seedling high, leaf area, leaves area/seedling, root fresh weight. The highest significant values as interaction effect of iron chelate and nitrogen were found in seedling high, seedling diameter, leaves number, leaf area, leaf area per seedling, total chlorophyll content and dry matter.
Keywords: Surface water,Dukan basin,Physicochemicalparameters,Phytoplankton